Synthesis Of New Schiff Bases As Materials For The Design Of Photovoltaics Cells - Kasmi-mir, S.; Elkebich, M.; Dembahri, Z.; Haouzi, A.; Kirsch, G. (University of Eloued جامعة الوادي, 2016)
We describe the synthesis of new organic Schiff bases chromophores 5 containing a rhodanine-3- acetic as electron accepteur moiety. Imines 3 were obtained by a condensation reaction from a lead molecule, the aminothiazolinethione 1 with versatile commercial aldehydes. The structure of all the compounds obtained was determined by the spectroscopic methods (IR, 1H NMR and 13C NMR). The study of UV-Vis imines 3 and 5 in methanol exhibit the phenomenon of π delocalized electrons responsible for the bathochromic effect.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: Aminothiazolinethione; iminomerocyanines; chromophores; rhodanine; bathochrome effect.